2004
DOI: 10.2134/jeq2004.4190
|View full text |Cite
|
Sign up to set email alerts
|

Field Studies on Exposure, Effects, and Risk Mitigation of Aquatic Nonpoint‐Source Insecticide Pollution: A Review

Abstract: Recently, much attention has been focused on insecticides as a group of chemicals combining high toxicity to invertebrates and fishes with low application rates, which complicates detection in the field. Assessment of these chemicals is greatly facilitated by the description and understanding of exposure, resulting biological effects, and risk mitigation strategies in natural surface waters under field conditions due to normal farming practice. More than 60 reports of insecticide-compound detection in surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
260
0
15

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(284 citation statements)
references
References 221 publications
(260 reference statements)
9
260
0
15
Order By: Relevance
“…Permethrin, like other pesticides and agricultural pollutants, can end up in aquatic receiving systems in a variety of ways; however, it is most often as a result of runoff generated either from an irrigation release or from a storm event (Schulz 2004). Willis et al (1986Willis et al ( , 1994 conducted studies on permethrin washoff from cotton plants as a result of rainfall.…”
Section: Discussionmentioning
confidence: 99%
“…Permethrin, like other pesticides and agricultural pollutants, can end up in aquatic receiving systems in a variety of ways; however, it is most often as a result of runoff generated either from an irrigation release or from a storm event (Schulz 2004). Willis et al (1986Willis et al ( , 1994 conducted studies on permethrin washoff from cotton plants as a result of rainfall.…”
Section: Discussionmentioning
confidence: 99%
“…In many Midwestern streams, agrichemical concentration is seasonal with the highest concentrations occurring during the spring (Kolok et al 2014). As a pollutant mixture, agricultural runoff contains fertilizers (Kaushal et al 2011), pesticides (Schulz 2004;Vecchia et al 2009;Lerch et al 2011a), and veterinary pharmaceuticals (Kolok and Sellin 2008;Biswas et al 2013;Jaimes-Correa et al 2015) which move downstream as "pulses" that persist on an order of days to weeks depending on the hydrology of the affected watershed (Blann et al 2009). Throughout the spring there will be a series of short-term pulsatile events which in composite will make up the overall spring pulse .…”
Section: Introductionmentioning
confidence: 99%
“…Many aspects about the toxicity of pesticides are well know, in particular about their neurotoxic effects, in fact pesticides organophosphates and carbamates act as covalent and irreversible inhibitors of acetylcholinesterase, the key enzyme of the central nervous system. It has been reported that many organochlorine pesticides, such as DTT, methoxychlor and dieldrine [8] are identified as endocrine disrupters, even if organophosphorous and carbamate pesticides are less persistent in the environment with respect to the organochlorines, they are also present in food and in animals and humans [17,18], many evidences are collecting regard their effect as endocrine disrupters [17,[19][20][21].…”
Section: Pesticides As Endocrine Disruptersmentioning
confidence: 99%